Symbolic Meaning in Digital Political Practice: An Analysis of Political Language on Social Media in the 2024 Makassar Mayoral Election - Hasruddin Nur; A. Octamaya Tenri Awaru (Tamaddun Life, 2025)
This study examines the construction, circulation, and contestation of symbolic meaning in political language on social media during the 2024 Makassar mayoral election. In contemporary local elections, social media has become more than a channel for transmitting campaign information; it functions as a symbolic arena in which political identities, local cultural claims, and affective attachments are continuously produced and negotiated. Using symbolic interactionism as the main analytical framework, this qualitative case study analyzes verbal and visual campaign symbols circulated through candidates' official Instagram, X, and Facebook accounts, together with public audience responses in the form of comments, likes, shares, and discursive counter-narratives. The findings show that slogans, hashtags, local linguistic markers, cultural attire, religious icons, and urban landmarks were strategically deployed to construct candidates as populist, culturally rooted, religiously legitimate, and future-oriented figures. However, these symbols did not generate a single stable meaning. Supporters interpreted them as signs of representation, hope, and collective identity, whereas skeptical users reframed the same symbols as empty rhetoric, elite manipulation, or performative populism. The study concludes that social media transformed the Makassar mayoral election into a symbolic performance in which political legitimacy was shaped not only by programs and policy claims but also by the capacity to control, circulate, and defend meanings in digital public space. The article contributes to political communication studies by foregrounding a locally specific Eastern Indonesian case and by showing how symbolic interaction, platform affordances, and local cultural repertoires intersect in digital electoral politics.